2018
DOI: 10.1016/j.evolhumbehav.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Cultural differences in preferences for facial coloration

Abstract: Effects of facial coloration on facial attractiveness judgments are hypothesized to be "universal" (i.e., similar across cultures). Cross-cultural similarity in facial color preferences is a critical piece of evidence for this hypothesis. However, only two studies have directly compared facial color preferences in two cultures. Both of those studies reported that White UK and Black African participants showed similar preferences for facial coloration. By contrast with the cross-cultural similarity reported in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 27 publications
7
58
6
Order By: Relevance
“…Yet a recent report indicates that Asian participants from Malaysia find only a slight increase in carotenoid skin colour more attractive than the skin colour baseline [23]. A further report concludes that mainland Chinese participants do not find increased yellow skin pigmentation attractive [34]. Nonetheless, whatever the influence of culture on colour preferences, the current study found that Asian, Black and White participants from the UK were equally impressed by the impact of diet on skin colour.…”
Section: Discussioncontrasting
confidence: 58%
“…Yet a recent report indicates that Asian participants from Malaysia find only a slight increase in carotenoid skin colour more attractive than the skin colour baseline [23]. A further report concludes that mainland Chinese participants do not find increased yellow skin pigmentation attractive [34]. Nonetheless, whatever the influence of culture on colour preferences, the current study found that Asian, Black and White participants from the UK were equally impressed by the impact of diet on skin colour.…”
Section: Discussioncontrasting
confidence: 58%
“…A further related study using calibrated images and monitors asked mainland Chinese and UK-based Caucasian participants to choose which is more attractive from pairs of yellowness faces, suggesting cross-cultural differences in colour preferences (Han et al, 2017). Relatedly, Tan et al (2017)…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Accordingly, it is the best understood portion of the impression formation problem. Researchers have long documented the structural and dynamic aspects of the face linked to impressions, including face-width, skin color, eye size, symmetry, emotional expression, head posture, and more (Adams & Kleck, 2003;CarrĂ©, Morrissey, Mondloch, & McCormick, 2010;Han et al, 2018;Hehman, Flake, & Freeman, 2015;Hehman, Leitner, & Gaertner, 2013;Jones, DeBruine, & Little, 2007;Said, Sebe, & Todorov, 2009;Zebrowitz, Fellous, Mignault, & Andreoletti, 2003).…”
mentioning
confidence: 99%